INTEGRATIVE APPROACHES TO FINANCIAL FORECASTING IN THE HOSPITALITY SECTOR - A COMPREHENSIVE ANALYSIS OF HOTEL TAMIŠ - Ćosić, Nenad; Miloš; Božić, Aleksandar (The Business of Tourism, 2025)
This paper explores the financial forecasting models applied to the matinee services at hotel Tamiš, which encompass food, drinks, and music offerings, over the period from July 1, 2023, to July 1, 2024. Utilizing SPSS 26. for comprehensive financial analysis, the study examines key metrics such as total revenue, raw material costs, and profit margins associated with these services. Findings indicate that effective management of raw material costs, which account for a significant portion of expenses, alongside strategic pricing, plays a crucial role in enhancing overall profitability. The integration of diverse revenue streams from food, drinks, and live entertainment is highlighted as a key factor in optimizing financial performance. The paper emphasizes the importance of adapting services to meet guest expectations and suggests avenues for future research, including the impact of guest’s feedback on the success of matinee offerings in the hospitality sector.